2021
DOI: 10.3390/v14010046
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of CD56dimCD16neg NK Cell Subset and Increased Inhibitory KIRs in Hospitalized COVID-19 Patients

Abstract: Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) infection induces elevated levels of inflammatory cytokines, which are mainly produced by the innate response to the virus. The role of NK cells, which are potent producers of IFN-γ and cytotoxicity, has not been sufficiently studied in the setting of SARS-CoV-2 infection. We confirmed a different distribution of NK cell subsets in hospitalized COVID-19 patients despite their NK cell deficiency. The impairment of this innate defense is mainly focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
(47 reference statements)
3
14
2
Order By: Relevance
“…observed an expansion of the CD56 dim CD16 neg NK subset and lower cytotoxic capacities in COVID-19 patients (32). Our results agree with the reports stating that SARS-CoV-2specific NK cell-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) responses were subjected to NK cell FcγRIIIa genetic variants (33) and the normal activity of NK cells might improve the control of COVID-19 by fighting the virus and suppressing fibrosis progression (34,35).…”
Section: Discussionsupporting
confidence: 91%
“…observed an expansion of the CD56 dim CD16 neg NK subset and lower cytotoxic capacities in COVID-19 patients (32). Our results agree with the reports stating that SARS-CoV-2specific NK cell-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) responses were subjected to NK cell FcγRIIIa genetic variants (33) and the normal activity of NK cells might improve the control of COVID-19 by fighting the virus and suppressing fibrosis progression (34,35).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the assessment of NK cells based on CD56, CD16, and KIRs expression in hospitalized COVID-19 patients indicated that a higher frequency of KIR2DL1 inhibitory receptor was concomitant with reduction of CD56dimCD16dim and CD56dimCD16bright NK Cell Subsets. Interestingly, this outcome was in parallel with CD56dimCD16neg NK Cell Subset expansion and higher frequency of KIR2DL1 and KIR2DL1/S1 inhibitor receptors ( 95 ). In line with this result, there is NK cell’s ADCC activity that results from the expression of CD16 on NK cells as an FC receptor, allowing the detection of antibody-coated infected and cancerous cells ( 72 ), hence the lack of CD16 expression could be associated with COVID19 severity.…”
Section: Nk Cells During Covid-19 Infection and Recovery Stagementioning
confidence: 99%
“…Besides, the CD56dimCD16pos NK cell subset with increased KIR expression was found in the lungs ( 94 ). Notably, immune-modulating occurs through KIR receptors of NK cells, playing a significant role against SARS-CoV-2 infection ( 95 ), and expression of CC chemokine receptor ( CXCR) 3, CXCR6, CCR5 on NK cells could cause the homing event developing in BAL of COVID-19 patients. In this regard, these markers, especially CCR6, could be considered risk factors in developing severe COVID-19 ( 72 ).…”
Section: Nk Cells During Covid-19 Infection and Recovery Stagementioning
confidence: 99%
“…Wang et al dynamically analyzed the evolution of the immune cells in COVID-19 patients and found that in those with fatal outcome, the NK cells gradually declined, while in survivors, NK cells increased from the onset to the late stage of the disease [ 27 ]. A recent study that analyzed the NK subtypes reported a significantly lower frequency of CD16 high CD56 dim NK subsets with subsequently higher expression of inhibitory receptors in COVID-19 patients compared to naïve and convalescent subjects, with no difference in CD56 high NK cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several subtypes of NK cells emerged after analyses of peripheral blood mononuclear cells (PBMC) in healthy subjects, as well as in those infected with Human Immunodeficiency Virus (HIV) [ 7 ] or SARS-CoV-2 viruses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%